Promoting a Syndemic Approach for Cardiometabolic Disease Management During COVID-19: The CAPISCO International Expert Panel - Al Mahmeed, Wael; Al-Rasadi, Khalid; Banerjee, Yajnavalka; Ceriello, Antonio; Cosentino, Francesco; Galia, Massimo; Goh, Su-Yen; Kempler, Peter; Lessan, Nader; Papanas, Nikolaos; Rizvi, Ali A.; Santos, Raul D.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Efforts in the fight against COVID-19 are achieving success in many parts of the world, although progress remains slow in other regions. We believe that a syndemic approach needs to be adopted to address this pandemic given the strong apparent interplay between COVID-19, its related complications, and the socio-structural environment. We have assembled an international, multidisciplinary group of researchers and clinical practitioners to promote a novel syndemic approach to COVID-19: the CArdiometabolic Panel of International experts on Syndemic COvid-19 (CAPISCO). This geographically diverse group aims to facilitate collaborative-networking and scientific exchanges between researchers and clinicians facing a multitude of challenges on different continents during the pandemic. In the present article we present our “manifesto”, with the intent to provide evidence-based guidance to the global medical and scientific community for better management of patients both during and after the current pandemic.